MALAT1 promotes platelet activity and thrombus formation through PI3k/Akt/GSK-3β signalling pathway - Jing Jiang; Daolai Zhang; Yeying Sun; Weihua Bian; Yan Lv; Jiahua Li; Xiaoli Jiang; Chunxiang Zhang (Stroke and Vascular Neurology)
Background Ischaemic stroke and other cardiovascular illnesses are characterised by abnormalities in the processes of thrombosis and haemostasis, which rely on platelet activity. In platelets, a wide variety of microRNAs (long non-coding RNA, lncRNAs) is found. Due to the absence of nuclear DNA in platelets, lncRNAs may serve as critical post-transcriptional regulators of platelet activities. However, research into the roles of lncRNAs in platelets is limited.Objective The purpose of this study is to learn more about the molecular mechanism by which MALAT1 affects platelet activity and thrombus formation.Methods/results The CD34+ megakaryocytes used in this research as an in vitro model for human megakaryocytes and platelets. Cell adhesion and spreading are enhanced in the absence and presence of agonists in CD34+ megakaryocytes subjected to MALAT1 knockdown (KD). The adhesion and activity of platelet-like particles produced by MALAT1 KD cells are significantly enhanced at rest and after thrombin activation. Thrombus development on a collagen matrix is also greatly enhanced in the microfluidic whole-blood perfusion model: platelets lacking MALAT1 exhibit elevated accumulation, distributing area and activity. In addition, MALAT1-deficient mice bleed less and form a stable occlusive thrombus more quickly than wild-type mice. PTEN and PDK1 regulated the activity of MALAT1 in platelets to carry out its PI3k/Akt/GSK-3β signalling pathway-related function.Conclusion The suppression of MALAT1 expression significantly increases platelet adhesion, spreading, platelet activity, and thrombus formation. lncRNAs may constitute a unique class of platelet function modulators.